2018
DOI: 10.1111/tpj.14031
|View full text |Cite
|
Sign up to set email alerts
|

Developmental role of the tomato Mediator complex subunit MED18 in pollen ontogeny

Abstract: Pollen development is a crucial step in higher plants, which not only makes possible plant fertilization and seed formation, but also determines fruit quality and yield in crop species. Here, we reported a tomato T-DNA mutant, pollen deficient1 (pod1), characterized by an abnormal anther development and the lack of viable pollen formation, which led to the production of parthenocarpic fruits. Genomic analyses and the characterization of silencing lines proved that pod1 mutant phenotype relies on the tomato SlM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…9f). In a recent study we characterized a tomato mutant ( pollen deficient1 , pod1 ), which also displayed a significant reduction of pollen viability and yielded parthenocarpic fruits [75]. We also reported that the loss-of-function of MEDIATOR COMPLEX SUBUNIT 18 ( POD1 / SlMED18 ) is responsible for the alterations in reproductive development observed in pod1 .…”
Section: Resultsmentioning
confidence: 99%
“…9f). In a recent study we characterized a tomato mutant ( pollen deficient1 , pod1 ), which also displayed a significant reduction of pollen viability and yielded parthenocarpic fruits [75]. We also reported that the loss-of-function of MEDIATOR COMPLEX SUBUNIT 18 ( POD1 / SlMED18 ) is responsible for the alterations in reproductive development observed in pod1 .…”
Section: Resultsmentioning
confidence: 99%
“…To silence the VIPP1 gene, an interference RNA (RNAi) construct was generated as described in Perez-Martin et al (2018) , with some modifications. A 326-bp fragment of Solyc11g008990 cDNA was amplified using the VIPP1-RNAi_F/R primers and cloned in sense and antisense orientations into the pKannibal vector, as described in Wesley et al (2001) .…”
Section: Methodsmentioning
confidence: 99%
“…Previous elegant studies have demonstrated that the temporal action of PCD in tapetal cells is critical for guarding the development of pollens and plant fertility (Chen & Liu, ; Tang et al , ). Although the timing of tapetal cell death initiation varies in different plant species, delayed or premature occurrence of PCD in tapetal cells in Arabidopsis, tomato ( Solanum lycopersicum ) and rice can cause strong defects in pollen development and thereby result in male sterility (Kawanabe et al , ; Ji et al , ; Pérez‐Martín et al , ).…”
Section: The Roles Of Autophagy In Key Processes Of Plant Reproductionmentioning
confidence: 99%